2002
DOI: 10.1038/nrm779
|View full text |Cite
|
Sign up to set email alerts
|

v-SRC'S hold over actin and cell adhesions

Abstract: The oncoprotein v-Src and its cellular homologue (c-Src) are tyrosine kinases that modulate the actin cytoskeleton and cell adhesions. Through the concerted action of their protein-interaction and kinase domains, they are targeted to cell matrix integrin adhesions or cadherin-dependent junctions between epithelial cells, where they phosphorylate substrates that induce adhesion turnover and actin re-modelling. Recent experiments have defined some of the key targets and effector pathways that mediate the pleiotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
232
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(243 citation statements)
references
References 112 publications
9
232
0
2
Order By: Relevance
“…We observed numerous dense, actin-rich, ring structures in v-Src transformed cells that had the appearance of podosomes (upper left panel). Additional staining for cortactin (lower left panel), an F-actin bundling protein that distinctly localizes to podosomes [28,30], confirmed that the structures were podosomes. We observed a striking disassembly and disappearance of podosomes in the RACK1-overexpressing cells (right panels).…”
Section: Rack1 Expression Alters Cytoskeletal Features Of V-srcmentioning
confidence: 89%
See 1 more Smart Citation
“…We observed numerous dense, actin-rich, ring structures in v-Src transformed cells that had the appearance of podosomes (upper left panel). Additional staining for cortactin (lower left panel), an F-actin bundling protein that distinctly localizes to podosomes [28,30], confirmed that the structures were podosomes. We observed a striking disassembly and disappearance of podosomes in the RACK1-overexpressing cells (right panels).…”
Section: Rack1 Expression Alters Cytoskeletal Features Of V-srcmentioning
confidence: 89%
“…transformed cells A rapid consequence of activation of v-Src is the replacement of organized actin stress fibers and focal adhesions (into which the actin fibers are tethered) with actin-rich ring structures called podosomes [27,28]. While podosomes contain similar proteins to those found in focal adhesions, their architecture is distinct in that podosomes do not have actin stress fibers tethered to them, but rather have a peculiar structure with an actin core [29] surrounded by a membrane domain enriched in integrins and adaptor proteins such as vinculin and paxillin.…”
Section: Rack1 Expression Alters Cytoskeletal Features Of V-srcmentioning
confidence: 99%
“…MEKK1 and FAK, both upstream regulators of ERK in some circumstances, are required for calpain activity, since cells deficient in these proteins exhibit lower calpain activity and reduced migration [193]. Further, calpain proteolysis of Rho removes the lipid-bearing membrane targeting sequence from active Rho thereby disrupting localized Rho signaling [194], and calpain-mediated proteolytic inactivation of WASP, cortactin and spectrin may result in F-actin turnover [195,196].…”
Section: Regulation Of Focal Adhesions and Actin By Proteolysismentioning
confidence: 99%
“…One might speculate that proteolysis of FAK is a negative feedback event that prevents liberated FAK from destabilizing adjacent adhesions. However, it should be noted that calpain cleavage of FAK may be restricted to v-src-transformed cells [141,196].…”
Section: Regulation Of Focal Adhesions and Actin By Proteolysismentioning
confidence: 99%
“…src64 is a Drosophila homologue of vertebrate c-src, a proto-oncogene encoding a nonreceptor tyrosine kinase that regulates adhesion, cell cycle progression, migration, apoptosis, development, angiogenesis, tumor invasion, and metastasis (Frame, 2002;Harrison, 2003;Thomas and Brugge, 1997;Tweedie et al, 2009;Yeatman, 2004). Both c-src and src64 have been implicated in regulating several microfilament cytoskeleton-associated cellular processes Frame et al, 2002;Guarnieri et al, 1998;O'Reilly et al, 2006;Roulier et al, 1998;Tateno et al, 2000;Thomas and Wieschaus, 2004;Thomas and Brugge, 1997).…”
mentioning
confidence: 99%